CAB International Regional Office for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In March 1995 CAB International opened a Regional Office for Africa in Nairobi, complementing its existing offices in the Caribbean and Asia. The short term priorities for the Regional Office are to strengthen links with member countries and to...